Isolation and fractionation of cellulose nanocrystals from kenaf core - Hanisah Syed Sulaiman,; Chi, Hoong Chan; Chin, Hua Chia; Sarani Zakaria,; Sharifah Nabihah Syed Jaafar, (Universiti Kebangsaan Malaysia, 2015)
In this study, cellulose nanocrystals (CNC) were produced using acid hydrolysis method. Kenaf core was pretreated with 4 wt. % sodium hydroxide (NaOH), followed by bleaching using 1.7 wt. % sodium chlorite (NaClO2) in acetate buffer. The bleached fiber was acid hydrolyzed for 45 and 55 min using 64 wt. % sulfuric acid (H2SO4). The size distribution of the CNC segregated via differential centrifugation with different speed was also investigated. The CNC suspension obtained was centrifuged at 3000, 6000, 9000 and 12000 rpm. The resultant CNC suspension collected was characterized using Fourier transform infrared (FTIR) analysis, X-ray diffraction (XRD) and transmission electron microscopy (TEM). FTIR results showed the progressive removal of non-cellulosic constituents for each subsequent treatment. It also showed that the CNC produced after hydrolysing for 55 min has the highest degree of crystallinity (81.15%). CNC produced from acid hydrolysis process of 45 min have lengths between 50 and 270 nm while CNC produced from acid hydrolysis process of 55 min have length around 40 to 370 nm.